2018
DOI: 10.1103/physrevb.97.035202
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the class of isovalent antiperovskite alkaline-earth pnictide compounds

Abstract: The few reported members of the antiperovskite structure class Ae3P nAP nB of alkaline earth (Ae = Ca,Sr,Ba) pnictides (P n = N,P,As,Sb,Bi) compounds are all based on the B-site anion P nB=N. All fit can be categorized as narrow gap semiconductors, making them of interest for several reasons. Because chemical reasoning suggests that more members of this class may be stable, we provide here a density functional theory (DFT) based survey of this entire class of 3 × 5 × 5 compounds. We determine first the relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…it is now considered that studying antiperovskites could enable to enlarge again more the range of applications [5,6] and of material candidates to display fundamental quantum properties, such as superconductivity [7] or topological electronic structures [8][9][10]. Understanding, functionalizing and optimizing these properties in a new class of materials requires extensive efforts to characterize their heterostructures and to develop an engineering of defects, surfaces and interfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…it is now considered that studying antiperovskites could enable to enlarge again more the range of applications [5,6] and of material candidates to display fundamental quantum properties, such as superconductivity [7] or topological electronic structures [8][9][10]. Understanding, functionalizing and optimizing these properties in a new class of materials requires extensive efforts to characterize their heterostructures and to develop an engineering of defects, surfaces and interfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…About a dozen compounds have nonzero Z 2 invariants in the assumed cubic structure. 21 The surface spectrum was obtained by first obtaining the maximally-localized Wannier functions and corresponding hopping amplitudes. 26,27 A semi-infinite system is then constructed and the surface spectrum is calculated using the iterative surface Green's function method 28,29 with a tight binding hopping cut-off of 4 unit cells.…”
Section: Structure Notation and Methodsmentioning
confidence: 99%
“…The antiperovskite (APv) structure class of alkaline earth and pnictides compounds has been proposed to harbor potential topological insulating phases. 20,21 Our density functional theory based survey of the entire class of 3 × 5 × 5 possible alkaline earth-pnictide APv compounds, 21 viz. Ae 3 P n A P n B , where Ae = Ca, Sr, Ba and P n A , P n B = N, P, As, Sb, Bi, confirmed that some of these compounds in the assumed cubic structure host, or are very close to, non-trivial topological phases.…”
Section: Introductionmentioning
confidence: 99%
“…221) but with anion and cation positions interchanged in the unit cell (7). Like their oxide perovskite counterparts, antiperovskite materials show a variety of tunable physical properties, including superconductivity, itinerant antiferromagnetism, giant magnetoresistance, large magnetovolume effects, and topological electronic behavior (8)(9)(10)(11)(12)(13)(14)(15). Among anti perovskite materials, transition metal (TM)-based nitride compounds (M 3 XN; M: TM; X: metallic or semiconducting element) are particu larly interesting as their physical behaviors are remarkably sensitive to external perturbations such as magnetic fields, temperature, or pres sure (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%